1447 Weighting the Factors Associated with Children Obesity: An International Perspective Toward an Unified Model. (October 2012) - Gregori, D; Baldi, I
Abstract : Beside genetic predisposition, several factors have been proposed to promote overweight and eventually obesity in children, from the socio- and built- environment down to behavioural attitudes (Bouchard, 2007). How this model is shared by different cultural settings is however unclear and less investigated. Using a unified protocol for data collection, a cross-sectional study has been performed on 960 children in India, Italy, Germany, France, UK, Argentina, Mexico and Brazil. Children CDC z-scores for BMI have been evaluated in association with several known factors influencing overweight and obesity (maternal and neonatal aspects, socio-economic familiar status, BMI of parents, physical activity, nutrition habits, screen activities). Based on a random-effect mixed effect model and the Kullback-Leibler Entropy Measure, the capability to explain variability in BMI of such factors has been computed. Percentages of explained variation are given as follows: India 41.4%, Italy 46.6%, Germany 65.6%, France 52.3%, UK 70.1%, Argentina 62.3%, Brazil 59.7%, Mexico 58.2%. Capability of proposed factors to capture variability in BMI is significantly higher in UK (p=0.03) than in other countries, being significantly lower in an emerging country like India (p=0.042). These results may suggest that more intense research should be specifically targeted to capture risk factors which are specific for that given cultural setting in addition to the general ones.